Treatment of modifiable risk factors for foot ulceration in persons with diabetes: a systematic review. (19th January 2020) - van Netten, Jaap J.; Sacco, Isabel C.N.; Lavery, Lawrence A.; Monteiro‐Soares, Matilde; Rasmussen, Anne; Raspovic, Anita; Bus, Sicco A.
Abstract: Background: Prevention of diabetic foot ulcers is important. Preventative treatment mostly targets and aims to improve modifiable risk factors of foot ulceration. While effectiveness of interventions in ulcer prevention has been systematically reviewed, their effectiveness in improving modifiable risk factors is unknown. Methods: The available medical scientific literature in PubMed, Excerpta Medica Database, and the Cochrane database was searched for original research studies on six interventions to treat modifiable risk factors for diabetic foot ulceration (ie, education for patients; education for professionals; self‐management; pre‐ulcer treatment; orthotic interventions; and foot‐ and mobility‐related exercises). We assessed interventions for eight outcomes (ie, patients' knowledge; treatment adherence; professionals' knowledge; pre‐ulcers; mechanical stress; neuropathy symptoms; foot/ankle joint mobility; and foot function). Both controlled and noncontrolled studies were selected. Data from controlled studies were assessed for methodological quality by two independent reviewers and extracted and presented in evidence and risk of bias tables. Results: We included 72 publications (26 with a controlled study design and 46 noncontrolled). We found that structured education may improve foot self‐care behaviour of patients, yearly foot examinations, and foot disease knowledge of health care professionals. Callus removal reduces peak plantar pressure. Custom‐made therapeutic footwear can be effective in reducing plantar pressure and may reduce callus. Foot‐ and mobility‐related exercises may improve neuropathy symptoms and foot and ankle joint range of motion, while they do not seem to reduce peak plantar pressure; evidence for their effect on foot strength is conflicting. Conclusions: Structured education for patients and health care professionals, callus removal, custom‐made therapeutic footwear, and foot‐ and mobility‐related exercises may be beneficial for improving modifiable risk factors for foot ulceration. However, we generally found low quality of evidence for interventions targeting modifiable risk factors for ulceration in persons with diabetes, with frequently inconsistent or limited results available per intervention and outcome.